Organic chromium supplementation in the diet of three porcine genotypes with different growth potential: effects on growth, metabolites, hormones, and carcass traits - Falcón Martínez, Jovita; Domínguez Vara, Ignacio Arturo; Pescador Salas, Nazario; Trujillo Gutiérrez, Daniel; Bórquez Gastelum, José Luis; Sánchez Torres, Juan Edrei; Morales Almaraz, Ernesto; Mondragón Ancelmo, Jaime; Rodríguez Gaxiola, Miguel Angel; Velázquez Garduño, Gisela; Grigioni, Gabriela Maria; Grageola Nuñez, Fernando (Canadian Science Publishing, 2025)
Chromium (Cr) potentiates insulin, influences the weight gain composition and carcass through changes in metabolites and hormones. The aim was to analyze the performance, carcasses, metabolites, and hormones of three porcine genotypes, G1 = Mexican Hairless × Yorkshire, G2 = Asian × Mexican Hairless, and G3 = Asian × Yorkshire, males and females with dietary Cr-L methionine (Cr-Met) (0.250 mg kg−1 DM). The experimental design was completely randomized factorial (3-genotypes × 2-sex × 2-Cr levels). The fattening with 84 pigs, live weight (LW) = 20.65 ± 0.68 kg, lasted 126 days, and were slaughtered. Thirty-six pigs were sampled to analyze metabolites and hormones in blood. The G1 ingested more (P = 0.04) total and daily dry matter (DMTI, DDMI). G2 and G3, and Cr-Met improved daily weight gain (DWG) and feed conversion (FC) (P = 0.05). Cr-Met reduced glucose (P = 0.05). Genotype, sex, and Cr-Met did not affect hormone levels (P > 0.05). G3 and Cr-Met increased HCW and CCW; Cr-Met reduced back fat (P = 0.05). We concluded that G2 and G3 had better DWG and FC; Cr-Met improved DWG and FC. Cholesterol was different between genotypes and sexes; Cr-Met reduced the glucose level. The levels of hormones were similar. The HCW and CCW of G2 and G3, sows and Cr-Met were higher; Cr-Met reduced the BF12thR.